Peningkatan Nilai Ekonomi Singkong Melalui Pengolahan Menjadi Stik Singkong di Desa Alai Selatan - Meisin Siti Zahara; Indri Ayuni Oktavani; Diah Ayu Pramisti; Zenal Mutaqin; Yeni; Lukita Tripermata (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Cassava is a food ingredient that contains carbohydrates, therefore cassava is considered an alternative food to replace rice in several villages in question in South Alai Village, Lembak District, Muara Enim Regency, South Sumatra. This cassava plant is very widely found throughout the village, but the cassava produced is only sold in the form of raw goods. Therefore, it is necessary to increase processed cassava into a product to increase selling value. This activity is of course to help the community how to process cassava, which is one of the potential of the village, into a high-value product and a business opportunity to increase economic income in South Alai Village. The method of implementing this activity uses demonstrations in the form of training, namely the practice of making processed cassava plants which was attended by the people of South Alai Village. After the implementation of this community service activity, participants have gained new insights and experiences.